(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تسعى الدول الرأسمالية الكبرى ومن بينها الولايات المتحدة الامريكية لبسط نفوذها في العالم وتحقيق مطامعها وحماية مصالحها من خلال التدخل في شؤون الدول المستضعفة ذات الأهمية العظمى لاقتصادياتها من حيث كونها مصادر للطاقة وأسواق لتصريف منتجاتها ومن خلال ما تدره لها من أموال وأرباح خيالية نتيجة لاستغلالها ونهب ثرواتها. فهي تسعى لإبقاء هذه الشعوب تابعة لها اقتصادياً وسياسياً وعسكرياً متبعة أساليب عديدة من خلال إبقاءها في حالة من الفوضى والفساد والنزاعات المستمرة لكي تبرر تدخلها تحت غطاء الأمم المتحدة باسم المهمات الإنسانية وبذلك تبرز كقوة عظمى تحقق الأمن والسلام في العالم. يهدف البحث إلى دراسة دور الاستراتيجية الامريكية في عسكرة النظام العالمي والهيمنة على الدول النامية كذلك دراسة دور النفط والمال و العسكرة وأزمات النظام الرأسمالي في تبعية البلدان النامية للدول المتقدمة واستمرار النزاعات فيها. وتوصلت الباحثة إلى عدة نتائج أهمّها: توجد علاقة بين الاستراتيجية الامريكية والهيمنة على البلدان النامية من خلال استمرار تبعية البلدان النامية لها . كما توجد علاقة وطيدة بين كل من النفط والمال و العسكرة وأزمات النظام الرأسمالي وبين النزاعات في البلدان النامية. The major capitalist countries including United States of America seek to extend their influence in the world and achieve their ambitions and protect their interests by intervening in the affairs of the vulnerable countries, which have great importance to their economies in terms of energy sources, and markets for the disposal of their products, and through the money, they generate. There fore they seek to keep these countries economically, politically and militarily following many methods by keeping them in a state of chaos, corruption and ongoing conflict to justify their intervention under the guise of the United Nations in the name of humanitarian missions and thus stand out as a superpower to achieve peace and security in the world. The study aims to study the relationship between the USA strategic in militarizing the world order and dominating the economies of developing countries.oil, militarization, and crises of the capitalist system in the subordination of the developing countries to the developed countries, and the continuation of conflicts in them. The researcher reached several results, the most important: There is a relationship between the USA strategic in dominating the economies of developing countries. There is also a relationship between oil, money, militarism, crises of the capitalist system, and conflicts in developing countries.